Impact of Adding Enzyme-Enriched Soybean Hulls to the Diet on Some Productive Traits of Broiler - Sharif Al-Ghazzi, Miad Mohammed; Hussein AL Machi, Abbas Salim; A Al-Ardhi, Saad A. (International Journal of Aquatic Research and Environmental Studies, 2026)
This study was conducted at the poultry farm of the Animal Production Department, College of Agriculture, Al-Muthanna University, from February 1, 2025, to March 8, 2025. 225 one-day-old broiler chicks were used. They were randomly distributed into five treatments with three replicates per treatment. The treatments were as follows: T1: Control (no additives). Treatments T2, T3, T4, and T5, an enzyme mixture (β-xylanase 2000 IU + β-glucanase 100 IU + cellulase 500 IU) was added at levels of 250, 500, 750, and 1000 gm ton of feed, respectively. The results of this study show that the use of soybean hulls enhanced with a mixture of enzymes (β-xylanase, β-glucanase, and cellulase) in broiler chicken diets, led to a significant improvement (P≤0.05) on some productive performance of broilers.